2021
DOI: 10.2186/jpr.jpr_d_21_00154
|View full text |Cite
|
Sign up to set email alerts
|

Reference value of masticatory performance by measuring the amount of glucose extraction from chewing gummy jelly

Abstract: Therefore, in this study, the AGE of adults with completely natural dentition was investigated to clarify the reference value of MP by measuring the AGE from chewing gummy jelly. Clarifying the reference value of AGE in healthy adults with natural dentition is clinically significant, because it can be used to evaluate the degree of masticatory performance and the therapeutic effect, or to detect people with reduced masticatory performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…In the masticatory ability test, most of the measured values of free mastication, wearing PEEK crown sided mastication, and non-wearing PEEK crown sided in 20 subjects with 23 cases reached the glucose concentration that is within the healthy range for edentulous people, and it was found that the PEEK crowns provided sufficient masticatory strength. Twenty-three cases had glucose concentrations of 150 mg/dL or higher 30 , which is within the healthy range for edentulous subjects. Furthermore, there was no significant difference in masticatory ability between the same subject with and without PEEK crowns, which suggests that PEEK crowns might not reduce masticatory ability.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the masticatory ability test, most of the measured values of free mastication, wearing PEEK crown sided mastication, and non-wearing PEEK crown sided in 20 subjects with 23 cases reached the glucose concentration that is within the healthy range for edentulous people, and it was found that the PEEK crowns provided sufficient masticatory strength. Twenty-three cases had glucose concentrations of 150 mg/dL or higher 30 , which is within the healthy range for edentulous subjects. Furthermore, there was no significant difference in masticatory ability between the same subject with and without PEEK crowns, which suggests that PEEK crowns might not reduce masticatory ability.…”
Section: Discussionmentioning
confidence: 56%
“…Since previous papers have reported that masticatory ability tests performed twice have shown no difference in the results of each test, the present study was also conducted with one measurement for each site 35 . The standard value was set at 150 mg/dL or higher 30 , which is within the healthy range for edentulous individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the masticatory task, participants were asked to unilaterally masticate and then ingest three different types of test foods (Happy, Haihain, and Nuts) in a random order. Subjects were asked to masticate on their preferred/habitual masticatory side that was determine in a previous study ( Sano and Shiga, 2021 ; Shiga et al, 2021 ), where subjects were asked to masticate on a gummy jelly test food and report the side on which mastication appeared to be easier.…”
Section: Methodsmentioning
confidence: 99%
“…Occlusal force and masticatory performance are widely used as objective parameters of masticatory function [1][2][3]. As ways of measuring occlusal force, methods using a strain gauge transducer, piezoresistive transducer, pressure transducer, or pressure-sensitive film have been reported.…”
Section: Introductionmentioning
confidence: 99%